FRI0028 Development and implementation of an educational video that instructs patients with rheumatoid arthritis for self-assessment of disease activity: methodology of the auto-das in middle eastern arab countries study. (12th June 2018) - Ziade, N.; Abi Karam, G.; Daher, A.; Abu Jbara, M.; Ayko, A.; Alam, E.; Arayssi, T.; Badsha, H.; al Emadi, S.; Halabi, H.; Harifi, G.; Khan, B.; et al.
Abstract : Background: Using a treatment target in rheumatoid arthritis (RA), such as DAS-28 and involving patients in their disease management can improve prognosis. Objectives: To develop and implement an educational video that instructs patients with RA for self-assessment of disease activity using DAS-28. Methods: Step 1:Initiation. Rheumatologists from some Middle Eastern Arab countries were invited to participate in this study. International experts and societies were contacted to access pre-existing educational material. Step 2: Development. Different material sources were synthetized and translated into Arabic and validated by the rheumatologists. The educational video was shot by a professional team with a real patient and a rheumatologist on set. Step 3. Validation. The final products (leaflets and video) were validated by the rheumatologists and tested with patients (figure 1). Obstacles were noted at the various study levels. Results: 23 rheumatologists from 7 Middle Eastern Arab countries participated in the study. A one-page educational leaflet was developed in Arabic and English languages. An educational video presenting the treat-to-target concept and the basics of DAS performance was produced in Arabic language with English subtitles. Obstacles at the rheumatologist, patient, cultural and logistic levels were identified and the potential solutions were addressed by the study team. Conclusions: Collaboration between several countries sharing the same language and similar cultural backgrounds was possible and able to produce an educational video aiming at the empowerment of RA patients for the self-assessment of their disease activity. The video will serve for future studies in the Arabic-speaking countries and will be available later for clinical use according to the rheumatologist's clinical judgment. References: [1] Smolenet al. Ann Rheum Dis2015;0:1–13. [2] Gossec, et al. Arthritis Rheumatol2016;68(suppl 10). [3] Studenic, et al. 2012;64(9):2814–23. www.nras.org.uk and www.das-score.nl Acknowledgements: Professor Maxime Dougados, Paris. Disclosure of Interest: None declared